An investigation into starting and closing telephone conversations between friends and relatives in American English and Vietnamese - Lê, Thị Quý (ĐHNN, 2017)
The purpose of this research is primarily to explore if there is a formula in casual telephone conversation openings as well as casual telephone conversation closings in Vietnamese. Then if there is, it examines how Vietnamese telephone openings and closings are realized between intimates in each part. Seconly, The study attempts to investigate similarities and differences in the ways American English and Vietnamese native speakers open and close telephone conversations.